2017
DOI: 10.1245/s10434-017-5789-3
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation is a Preferable Alternative to Palliative Therapy for Selected Patients with Advanced Hepatocellular Carcinoma

Abstract: Background:Patients with hepatocellular carcinoma (HCC) beyond the traditional criteria (advanced HCC) are typically offered palliation, which is associated with a 3-year survival rate lower than 30%. This study aimed to describe the outcomes for a subset of patients with advanced HCC who satisfied the Extended Toronto Criteria (ETC) and were listed for liver transplantation (LT). Materials & Methods: All patients listed in the Toronto liver transplant program with HCC beyond both the Milan and University of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…This indicates that the clinical relevance of IRI is limited to generally low-risk populations and diminishes with increasing tumour burden. This appears to be particularly importantly because it demonstrates the possibility of using high-risk grafts to expand the donor pool for high-risk HCC candidates in the context of discussion on widening the boundaries of existing selection criteria 2 6 , 29 . Notably, the safe use of extended criteria allografts preferentially for patients with advanced tumours was already reported 30 .…”
Section: Discussionmentioning
confidence: 98%
“…This indicates that the clinical relevance of IRI is limited to generally low-risk populations and diminishes with increasing tumour burden. This appears to be particularly importantly because it demonstrates the possibility of using high-risk grafts to expand the donor pool for high-risk HCC candidates in the context of discussion on widening the boundaries of existing selection criteria 2 6 , 29 . Notably, the safe use of extended criteria allografts preferentially for patients with advanced tumours was already reported 30 .…”
Section: Discussionmentioning
confidence: 98%
“…The Extended Toronto Criteria allow LT for patients with any number and any size of HCC lesions provided no evidence exists for vascular invasion or extrahepatic disease, no cancer-related constitutional symptoms are observed, and a targeted biopsy of the largest lesion does not show poor differentiation (39). Two studies evaluated these criteria in patients exceeding the Milan criteria and in patients exceeding the UCSF criteria and found 5-year overall survival rates of 69% and 66%, respectively, which was not significantly lower than in patients within the Milan criteria (39,40).…”
Section: Futility Rule #3: Presence Of Microvascular Invasion or Poormentioning
confidence: 99%
“…The most commonly used locoregional techniques are stereotactic body radiation, transarterial chemoembolization, transarterial radio-embolization, and radiofrequency ablation. Aravinthan et al [46] reported their outcomes after liver transplantation in patients with advanced HCC within extended Toronto Criteria.…”
Section: Locoregional Therapiesmentioning
confidence: 99%